Above are the hills and below is the city. Local categorizations and territorial construction of a Kolla community in the province of Salta (Huellas, 2024)
This research explores the local categorizations and the territorial construction of an indigenous kolla community in the Argentine Northwest (NOA), examining how they perceive and utilize various spaces within both rural and urban environments. By adopting a holistic understanding of their territory, this study considers both material and symbolic dimensions. Notably, spaces associated with dwellings and production areas (e.g., casas grandes, puestos, rastrojos, hoyadas, corrales) reveal complementarities. These spaces are organized locally through axe (e.g., arriba-abajo) and categorized with meaningful and affective distinctions (sacred spaces, cerros, campo, pueblo, barrio or ciudad). By using a transdisciplinary methodology, this study applies collaborative ethnography and social cartography to facilitate a co-constructive knowledge process, integrating local and academic expertise to promote alternative research approaches in the NOA.
Keywords: Territory; local knowledge; collaborative ethnography; Social cartography.